Archaeology and ethnoarchaeology in the Leliefontein reserve and surrounds, Namaqualand - Webley, L. E.(Lita Ethel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1984.